Imagery Ability and Imagery Perspective Preference: A Study of Their Relationship and Age- and Gender-Related Changes - Karen P. Y. Liu; Monica Lai; Shirley S. M. Fong; Michelle Bissett (Behavioural Neurology)
This study examined if imagery ability (i.e., vividness and temporal congruence between imagined and executed knee extensions) and imagery perspective preference were affected by ageing and gender. Ninety-four participants, 31 young, 43 intermediate, and 20 older adults completed the Vividness of Movement Imagery Questionnaire-2 and a knee extension temporal congruence test to reflect on their imagery ability and an imagery perspective preference test. Male participants had a better imagery ability than the female participants (F 4,85=2.84, p=.029, η2=.118). However, significant age-related changes in imagery ability were not found in the three age groups. Change in imagery perspective preference with a trend towards an external imagery perspective was observed with ageing (F 3,89=3.16, p=.028, η2=.096) but not between male and female. The results suggest that imagery ability may be preserved with ageing. As individuals age, their preference for using an imagery perspective shifts from a more internal to a more external perspective. This understanding is important when designing future imagery research and real-life application or clinical intervention.